Case Study on the Stability Control of Broken Surrounding Rock in Roadway Excavation on the Edge of a Collapsed Stope Area - Yabin Wu; Jianhua Hu; Chengyu Xie; Dongping Shi (Advances in Civil Engineering)
Predicting and controlling the collapse of surrounding rock (especially broken rock masses) in underground chambers is an important topic in mining and geotechnical engineering. Based on an example, this paper introduces a case study of surrounding rock stability control technology in stope mining around abandoned areas. Based on on-site coring, mechanical properties of rock samples, and on-site grouting reinforcement technology, the TRT6000 advanced geological prediction system was used to predict the stability status of the surrounding rock of the underground chamber. AUTODYNA software was used to build a dynamic coupling model for numerical simulation prediction and optimization of blasting parameters and to reveal the dynamic variation in the surrounding rock. The dynamic failure process of the surrounding rock of the chamber before and after optimization of the blasting parameters is simulated, and the deformation characteristics and damage and acoustic emission characteristics of the surrounding rock are clearly shown. The surrounding rock failure first appeared around the surface of the underground chamber because of the high stress concentration around the surface of the chamber after blasting; with the interaction between the explosive gas and the rock mass, the damaged area further propagated into the external rock, eventually leading to a large damage area. At the same time, there is a large tensile failure in the rock, resulting in expansion and rupture around the underground chamber. Finally, the 3D laser scanning method is used to verify the superiority of the optimized blasting initiation sequence. The new edge hole detonation sequence can effectively improve the blasting vibration and successfully control the further damage of the surrounding rock of the underground chamber, thus proving the edge hole drug pack. Moreover, the initiation mode of the delay stage of the side hole charge is determined. This study provides a useful reference for the stability control of surrounding rock in mining in mining areas.